THE CORRELATION BETWEEN COPING STRATEGY AND ACADEMIC RESILIENCE IN MEDICAL FACULTY STUDENTS - Nida Muhlisa; Nur Aeni (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2021)
The aim of this study was to examine the correlation between coping strategies and academic resilience in medical faculty students. The research subjects in this study were 70 active students of the Medical Faculty of Universitas Muhammadiyah Purwokerto who were selected using proportionate stratified random sampling. The data were analysed using the Analysis of Product Moment through the help of SPSS 22 for Windows. Correlation values r = 0.615 and p = 0.000 (p<0.01) was obtained in this study which indicated that there was a positive and significant correlation between coping strategies and academic resilience. Coping strategies provide an effective contribution of 37.8% to academic resilience. However, there are 62.2% of other factors such as strong social skills, interpersonal skills and social support that affect academic resilience.